Google Classroom as The Teaching Media Based on The Concept of Tat Twam Asi - Dewa Gede Bambang Erawan; I Gusti Ayu Putu Tuti Indrawati; A. A. Istri Yudhi Pramawati; Ratna Dwi Anjani Putri (Universitas Pendidikan Ganesha, 2022)
The current pandemic has caused a change in the learning system in Indonesia to be centered on online learning. Students, teachers, and parents are forced to be able to carry out online learning. Learning media can generate critical thinking processes and learning creativity, considering the many gaps in the learning process. Google Classroom learning media based on the concept of